The Fruits of Diversity and Globalization: Participation and Contributions of East-Asian Scholars in Public Administration. (22nd November 2022) - Zhang, Yahong; Holzer, Marc; Mao, Hanjin; Ding, Fangda; Li, Huafang
Abstract: The growth of East-Asian scholars in the American public affairs and administration (PA) field is increasingly apparent in recent years. Their participation demonstrates the diversity of the academic community and the globalization of higher education. However, little attention has been paid in the literature to this minority. From the broader perspective, Asian minorities have been overlooked in the discourse on diversity, equity, and inclusion, although they certainly confront social challenges such as inequity, injustice, discrimination, xenophobia, and even hate crimes. Our research attempts to address this gap in the literature by objectively documenting the participation and contributions of East-Asian scholars (EASs) to the American PA field. We find that across the top 100 PA schools, approximately 5% of the total full-time faculty members are East-Asian scholars, and that almost 20% of the peer-reviewed articles published in the top 10 PA journals are contributed by that scholarly community. However, the representation of East-Asian scholars in journal and association leadership teams remains low, which does not rise to their level of their contributions via peer-reviewed journal articles.